2013
DOI: 10.1007/s11999-013-2800-6
|View full text |Cite
|
Sign up to set email alerts
|

Tibia Vara Affects the Aspect Ratio of Tibial Resected Surface in Female Japanese Patients Undergoing TKA

Abstract: Background Tibia vara seen in Japanese patients reportedly influences the tibial component alignment when performing TKA. However, it is unclear whether tibia vara affects the component position and size selection. Questions/purposes We therefore determined (1) the amount of medial tibial bow, (2) whether the tibia vara influences the aspect ratio of the tibial resected surface in aligning the tibial component with the tibial shaft axis, and (3) whether currently available tibial components fit the shapes of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…In a TKA, the thickness of the tibial component is selected to restore the joint line and to match the contours of the resected surfaces [ 13 , 14 , 31 , 36 ]. Therefore, a superstructure of polyethylene is generally built above the posterolateral area of the tibial plateau, leading to a potential risk of popliteus impingement (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In a TKA, the thickness of the tibial component is selected to restore the joint line and to match the contours of the resected surfaces [ 13 , 14 , 31 , 36 ]. Therefore, a superstructure of polyethylene is generally built above the posterolateral area of the tibial plateau, leading to a potential risk of popliteus impingement (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Such that, studies have shown a lower prevalence of osteoporosis being found in the Chinese population than their Japanese counterparts [ 24 , 25 ]. Individual studies have also described the difference in morphologies of knee and proximal tibia between the Japanese and Korean population [ 26 , 27 ]. However, a study on the direct comparison among these Asian ethnicities remains to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] It has been reported that the proximal tibia vara involved the medial shift of the tibial articular surface (TAS). 4,[6][7][8] However, it is still obscure that the varus inclination of the TAS has a correlation with the medial shift of the TAS. The constitutional varus knee could be the consequence based on Hueter-Volkmann's law, which states that growth at the epiphyses is retarded by increased compression, whereas reduced loading accelerates growth.…”
Section: Introductionmentioning
confidence: 99%